Moving beyond the ‘black box’ approach to public interventions promoting research, development and innovation. The concept of behavioural additionality - Paulina Kubera (Studia i Materiały)
Traditional evaluations of public policy actions focus on the input and output side of the intervention (i.e. assume the so-called ‘black box’ approach), whereas the experience of public intervention also affects deeper changes of the recipient companies. Thus, a third dimension of additionality has been introduced to the evaluation theory and practice – the ‘behavioural additionality’. It takes account of the difference in behaviour of a target population owing to a public intervention. Although the idea to evaluate how public policy interventions affect behaviour of the actors of the innovation system appears to be a very compelling line of inquiry for scholars and practitioners alike, it gives rise to many practical difficulties. This paper investigates how behavioural additionality is defined and measured as well as what are the empirical findings on behavioural additionality in the literature on evaluation of public policy instruments in the field of research, development and innovation (RDI), where this term has been coined. To this end, a quantitative systematic literature review has been conducted. Thirty-eight scientific papers which explicitly acknowledge assessing behavioural additionality in reference to RDI policy instruments, and represent original research papers in which behavioural additionality is approached empirically, have been analysed revealing the current state in the field and directions for further research. Seven different conceptualisations of the term have been identified which reflect a multidimensional nature of the concept.